Biodiversity and Bionomics of the Black Flies (Diptera: Simuliidae) of Northeastern Algeria - Cherairia, Mouna; Adler, Peter H.; Samraoui, Boudjéma (Zootaxa, 2014)
Black flies in the Seybouse River Basin in northeastern Algeria were sampled at 31 sites along the main river and its tributaries across all seasons from 2011 to 2013. Eight nominal species and species complexes in three genera were identified among more than 31,000 specimens. Urosimulium faurei (Bernard, Grenier & Bailly-Choumara), Simulium (Eusimulium) mellah Giudicelli & Bouzidi, and Simulium (Nevermania) lundstromi (Enderlein) were recorded for the first time in northeastern Algeria. Three cytoforms of the Simulium (Eusimulium) velutinum complex and two morphoforms of Simulium (Nevermannia) ruficorne Macquart were found. The most abundant and ubiquitous taxon, Simulium (Wilhelmia) pseudequinum Segúy, representing nearly 80% of collected specimens, occupied the widest range of habitats, including those with anthropogenic influences.